Student Engagement in Sustainability through Work Placements - Cripps, Karen; Louw, Jonathan; Smith, Lani Meverly (GILE Journal of Skills Development, 2026)
Understanding how students engage with sustainability during work placements represents a critical gap in education for sustainable development. This study explores undergraduate Business School students’ engagement in and learning from sustainability-related projects during work placements. While existing research shows the benefits of placements for student learning and employability, sustainability-related engagement and learning are underexplored. This study addresses this gap through a qualitative study which explores the nature of sustainability-related placement roles, how placement learning experiences shape student development, and how sustainability-related experiences can be effectively embedded into university preparation processes. The findings indicate that, although sustainability is rarely explicit in placement role specifications, there are numerous opportunities to engage informally, particularly when students proactively seek them. Through the conceptual lenses of self-efficacy and career identity, the study provides recommendations for further research, educational institutions and workplace providers.